2010
DOI: 10.1074/jbc.m110.128330
|View full text |Cite
|
Sign up to set email alerts
|

ATBF1 Inhibits Estrogen Receptor (ER) Function by Selectively Competing with AIB1 for Binding to the ER in ER-positive Breast Cancer Cells*

Abstract: Loss of the q22 band of chromosome 16 is a frequent genetic event in breast cancer, and the candidate tumor suppressor gene, ATBF1, has been implicated in breast cancer by genomic deletion, transcriptional down-regulation, and association with better prognostic parameters. In addition, estrogen receptor (ER)-positive breast cancer expresses a higher level of ATBF1, suggesting a role of ATBF1 in ER-positive breast cancer. In this study, we examined whether and how ATBF1 affects the ER function in breast cancer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
87
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(91 citation statements)
references
References 48 publications
4
87
0
Order By: Relevance
“…We found that estrogen-ER signaling regulates ATBF1 by inducing its transcription while causing its protein degradation. Together with our earlier study (13), these results establish an autoregulatory feedback loop between ATBF1 and estrogen-ER signaling.…”
supporting
confidence: 50%
See 3 more Smart Citations
“…We found that estrogen-ER signaling regulates ATBF1 by inducing its transcription while causing its protein degradation. Together with our earlier study (13), these results establish an autoregulatory feedback loop between ATBF1 and estrogen-ER signaling.…”
supporting
confidence: 50%
“…RNA interference (RNAi)-RNAi against ATBF1 and ER genes was performed as previously described (13). Four ATBF1-specific siRNAs targeting different regions of the ATBF1 gene and the negative control siRNA against the luciferase gene, which does not match any human genomic sequences, were also described previously (13).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Zinc finger homeobox 3 (ZFHX3) is a transcriptional repressor of 3,703 amino acids containing one ATPase A-motif, two DEAH box-like sequences, four homeodomains, and 23 zinc finger motifs involved in transcriptional regulation ( Fig. 1) (Dong et al 2010). ZFHX3 inhibits the enhancer of the alpha-fetoprotein (AFP) gene by binding to its AT-rich core sequence, and it also regulates myoblasts differentiation through the binding to the AT-rich sequence of MYF6 promoter (Li et al 2013).…”
Section: Introductionmentioning
confidence: 99%